The Performance of Standard - Harms, Philip (My University, 2011)
The performance of the Yield Enhanced Security (YES) and the Yield Enhanced Security Plus (Yes-Plus) offered in South Africa by Standard Corporate and Merchant Bank was modelled over a ten-year period. Through combinations of put and call options on certain shares an investor stands to gain superior returns during periods of market consolidation. Such synthetic instruments are new to the South African market, and have yet to be the subject of extensive study. Daily closing share prices were collected over a ten-year period. A model simulating the instrument’s performance was built using Microsoft Excel. It was found that the YES outperformed the Yes-Plus and conventional share investment, both in terms of absolute, and risk-adjusted returns.
MBA - WBS
Keywords: Yield Enhanced Security; Yield Enhanced Security Plus; Put and call options; Options; Johannesburg Securities Exchange